Comment on a meta-analysis comparing hepatic resection or transarterial chemoembolization as initial treatment for hepatocellular carcinoma - Zhong JH; Xiang BD; Li LQ (Dove Medical Press, 2015)
Jian-Hong Zhong,1,2 Bang-De Xiang,1,2 Le-Qun Li1,2 1Hepatobiliary Surgery Department, Affiliated Tumor Hospital of Guangxi Medical University, Nanning, People’s Republic of China; 2Guangxi Liver Cancer Diagnosis and Treatment Engineering and Technology Research Center, Nanning, People’s Republic of China We read with great interest the meta-analysis by Tian et al1 comparing the efficacy of initial hepatic resection (HR) or transarterial chemoembolization (TACE) for patients with primary hepatocellular carcinoma (HCC). The results from this analysis of eleven cohort studies involving 6,297 patients suggested similar overall survival (OS) and recurrence rate for the two techniques. We believe this conclusion should be treated with caution because it conflicts with much larger original studies2,3 and large systematic reviews.4,5  View original article by Tian X, Dai Y, Wang DQ, et al.